Adapting a Remotely Delivered Patient Navigation Program for Colorectal Cancer Screening in Primary Care: Important Considerations for Rural Contexts - Brooke Ike; Gina A. Keppel; Katie P. Osterhage; Linda K. Ko; Allison Cole (SAGE Publishing, 2024)
Introduction: Colonoscopy is a critical component of colorectal cancer (CRC) screening and patient navigation (PN) improves colonoscopy completion. A lay navigator remotely providing navigation across rural primary care organizations (PCOs) could increase PN access. In preparation for the Colonoscopy Outreach for Rural Communities (CORC) study, we examined partners' perspectives on contextual factors that could influence CORC program implementation, and adaptations to mitigate potential barriers. Methods: We interviewed 29 individuals from 6 partner PCOs and the community-based organization (CBO) delivering the PN program. An analysis approach informed by Miles, Huberman, and Saldana identified critical themes. Results are reported using the Framework for Reporting Adaptations and Modifications-Enhanced (FRAME). Results: Potential barriers included that rural patients are hard to reach remotely and might mistrust the navigator, and the CBO is unfamiliar with the patient communities and does not have patient care experience or pre-existing communication pathways with the PCOs. Program content and navigator training was adapted to mitigate these challenges. Conclusions: Our study highlights contextual factors to account for before implementing a remote, centralized patient navigation program serving rural communities. Gathering partner perspectives led to intervention adaptations intended to address potential barriers while leaving the core components of the evidence-based intervention intact.